A nationwide study of social-emotional problems in young children in Turkey - AY, NADİYE PINAR (ELSEVIER SCIENCE INC, 2013)
We aimed to assess the prevalence of social-emotional problems of Turkish children in early childhood and to understand their association with various bio-psycho-social risk factors, in order to establish guidelines in planning training programs for parents and professionals. Data from a representative sample of 1507 boys (54.3%) and 1268 girls (45.7%) aged 10-48 months were collected. The primary caregivers (mothers = 91.4%) completed the Brief Infant-Toddler Social and Emotional Assessment (BITSEA), the Brief Symptom Inventory (BSI) and a form designed to gather information about various bio-psycho-social risk factors. Based on the caregiver terms, a total of 1626 children (60.1%) were reported to experience social-emotional problems. However, based on the BITSEA-problem clinical (1.5 SD) cut-off scores, 9.3% (9.1% of boys; 9.5% of girls) of all children were found to experience social-emotional problems. The variables, that showed a significant association with BITSEA-problem scores in pairwise comparisons, were entered in logistic regression analysis to determine the variables that predict the group with scores of above clinical cut-point. Higher total score of BSI of the primary caregiver, being separated from the mother for more than a month, and lower income of the family were found to be significant predictors of social-emotional problems. Caregiver reports highlight that maternal variables of mothers' psychological well-being, education and access to sources of support are closely related to the social-emotional wellbeing of their off-spring. The findings obtained from this study may be used for detection of prioritized domains in terms of management of preventive mental health services. (C) 2012 Elsevier Inc. All rights reserved.
Keywords: Toddler; Social-emotional; Psychiatry; Prevalence; Turkish children; PRESCHOOL-CHILDREN; EARLY-CHILDHOOD; MENTAL-HEALTH; INFANT; BEHAVIOR; TODDLERS; SCALE; MODEL; CARE